2022
DOI: 10.1186/s12943-022-01543-7
|View full text |Cite
|
Sign up to set email alerts
|

Liquid biopsy: a step closer to transform diagnosis, prognosis and future of cancer treatments

Abstract: Over the past decade, invasive techniques for diagnosing and monitoring cancers are slowly being replaced by non-invasive methods such as liquid biopsy. Liquid biopsies have drastically revolutionized the field of clinical oncology, offering ease in tumor sampling, continuous monitoring by repeated sampling, devising personalized therapeutic regimens, and screening for therapeutic resistance. Liquid biopsies consist of isolating tumor-derived entities like circulating tumor cells, circulating tumor DNA, tumor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
208
0
6

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 338 publications
(280 citation statements)
references
References 228 publications
1
208
0
6
Order By: Relevance
“…However, within the last years, most applications of ddPCR in cancers have focused on LBs, including ctDNA and ctRNA, EVs, and CTCs [ 77 ]. In contrast to highly invasive and spatially limited tissue biopsies, LBs allow for repeat sampling and longitudinal monitoring of disease progression over time, providing outstanding opportunities for the detection of MRD or therapy resistance, as well as recurrence or disease progression [ 222 ]. Nonetheless, research presented at the American Society of Clinical Oncology (ASCO) meetings highlighted how advances in dermato-oncology assisted by ddPCR and LBs may inform future research and clinical decisions in cutaneous tumors [ 223 , 224 , 225 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, within the last years, most applications of ddPCR in cancers have focused on LBs, including ctDNA and ctRNA, EVs, and CTCs [ 77 ]. In contrast to highly invasive and spatially limited tissue biopsies, LBs allow for repeat sampling and longitudinal monitoring of disease progression over time, providing outstanding opportunities for the detection of MRD or therapy resistance, as well as recurrence or disease progression [ 222 ]. Nonetheless, research presented at the American Society of Clinical Oncology (ASCO) meetings highlighted how advances in dermato-oncology assisted by ddPCR and LBs may inform future research and clinical decisions in cutaneous tumors [ 223 , 224 , 225 ].…”
Section: Discussionmentioning
confidence: 99%
“…These biomarkers offer complementary information at different levels. Numerous LB-based studies and clinical trials for a wide variety of cancer types (e.g., breast cancer, colorectal cancer (CRC), prostate cancer, non-small cell lung cancer (NSCLC), and malignant melanoma) have been initiated to demonstrate their clinical relevance in cancer patients [ 14 , 22 , 23 ]. The clinical utility of LB has been demonstrated for the detection of epidermal growth factor receptor (EGFR) mutations in NSCLC patients or for the detection of KRAS proto-oncogene, GTPase (KRAS) mutations in patients suffering from metastatic CRC [ 24 ].…”
Section: State Of Playmentioning
confidence: 99%
“…As a non-invasive and convenient sampling technique for tumor diagnosis, liquid biopsy has gradually replaced invasive methods for cancer diagnosis and detection in the last decade [ 93 ]. Meanwhile, an increasing number of studies have found that tsRNAs are present not only in the tissues, but also widely in the body fluids of cancer patients, including plasma, serum, and exosomes.…”
Section: Clinical Application Value Of Tsrnas In Cancer: As Biomarker...mentioning
confidence: 99%